2014
DOI: 10.1038/srep06478
|View full text |Cite
|
Sign up to set email alerts
|

Altered ghrelin levels in boys with autism: a novel finding associated with hormonal dysregulation

Abstract: Autism is a neurodevelopmental disorder with unclear pathogenesis. Many clinical observations and hormone studies have suggested the involvement of the neuroprotective hormone ghrelin in autism. The current study aimed to investigate the potential role of ghrelin in autism and to elucidate the associated hormonal dysregulation. This case-control study investigated acyl ghrelin (AG), des-acyl ghrelin (DG), total testosterone (TT), free testosterone (FT), leptin and growth hormone (GH) levels in 31 male children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 37 publications
5
27
1
Order By: Relevance
“…Since leptin is linked to ASD in several studies (Ashwood et al 2008; Blardi et al 2010; Rodrigues et al 2014; Al-Zaid et al 2014; Essa M.M. et al 2011), including ours, and adiponectin-leptin ratio is considered as a marker of metabolic syndrome (Inoue et al 2005), we assessed the association between log-transformed adiponectin-leptin ratio and subsequent ASD risk.…”
Section: Resultsmentioning
confidence: 99%
“…Since leptin is linked to ASD in several studies (Ashwood et al 2008; Blardi et al 2010; Rodrigues et al 2014; Al-Zaid et al 2014; Essa M.M. et al 2011), including ours, and adiponectin-leptin ratio is considered as a marker of metabolic syndrome (Inoue et al 2005), we assessed the association between log-transformed adiponectin-leptin ratio and subsequent ASD risk.…”
Section: Resultsmentioning
confidence: 99%
“…Beyond leptin's role in prenatal and postnatal weight gain, this pleiotropic cytokine has been shown to be important in the regulation of the immune system, neurodevelopment including neuron excitability, synaptic plasticity, neural differentiation and promoting migration of neuronal lineage cells to the cortical plate [Ashwood et al, ; Blardi et al, ; Harvey, ; Harvey, Solovyova, & Irving, ; Paz‐Filho et al, ]. Emerging evidence suggests that children (2–15 years) with ASD have significantly higher plasma leptin levels than controls [Al‐Zaid, Alhader, & Al‐Ayadhi, ; Ashwood et al, ; Blardi et al, ; Essa et al, ; Rodrigues et al, ]. Among a few studies that have researched leptin‐ASD association in children, most were done after ASD diagnosis [Ashwood et al, ; Blardi et al, ], thus unable to assess the temporal relationship.…”
Section: Introductionmentioning
confidence: 99%
“…The significant increase of free testosterone in a magnitude higher than that of total testosterone is explained by the lack of concomitant increase in SHBG. Both total testosterone and free testosterone were positively and strongly correlated with each other and both of which had a positive strong correlation with DHEA, which was also significantly elevated in autistic children by 50% suggesting an adrenal source of the elevated androgens [35]. Significant elevation of those androgens has been reported in American autistic children in comparison with laboratory reference values by Geier's study, which reported 158% increase in total testosterone, 214% increase in serum free testosterone, and 192% increase in DHEA [34].…”
Section: Hyperandrogenism In Autismmentioning
confidence: 90%
“…In the light of EMB theory of autism, numerous studies were conducted to investigate postnatal testosterone levels in autistic children. Although it has been demonstrated by some studies that children with autism have significantly elevated androgen levels [34,35], other studies by Tordjman et al [36] and Lutchmaya et al [37] have not found significant differences in testosterone levels in autism. Moreover, postpubertal androgen levels were found to be lower than controls in autistic children [38].…”
Section: Hyperandrogenism In Autismmentioning
confidence: 94%